Google dorks: Use cases and adoption study - Abasi, Reza (My University, 2020)
The information age brought about radical changes in our lives. More and more assets are getting connected to the Internet. On the one hand, the connectivity to this ever-growing network of connected devices and assets (the Internet) precipitates more convenience and access to various resources. However, on the downside, the Internet could be the hotbed for malicious actors like hackers, attackers, and cybercriminals’ communities. Continuous Penetration testing and monitoring of the sites, and forums providing illicit digital products and services is a must-do task nowadays. Advanced searching techniques could be employed for discovering such forums and sites. Google dorks that are utilizing Google’s advanced searching techniques could be applied for such purpose. Google dorks could be used for other areas that we will explain during this thesis in more detail like information gathering, vulnerability detection, etc. The purpose of this thesis is to propose advanced searching techniques that will help cybersecurity professionals in information gathering, reconnaissance, vulnerability detection as well as cyber criminal investigative tasks. Further, a usability study has been conducted to examine the acceptance of these techniques among a group of cybersecurity professionals. In this usability study, we will measure the significance of 5 variables in the innovation diffusion model (IDT) namely Complexity, Compatibility, Relative advantage, Trialability, and observability in the adoption of Google dorks for searchrelated tasks for cybersecurity professionals. Keywords: Google dorks, Cybercriminal forums, Information gathering, Dark web, Defaced sites, Innovation diffusion theory